In Silico Analysis and Docking Study of the Active Phyto Compounds of Ginkgo Biloba Against Alzheimer's Amyloid-Beta Protein - Suveena Rai; Shubham Wanarase (International Journal of Cell Biology and Cellular Functions, 2023)
Objective: Alzheimer's disease, an age-related progressive neurological condition, arises due to the accumulation of amyloid-beta protein within the brain. In this study, an attempt was made to explore the potential of natural compounds derived from Ginkgo, known for their diverse medicinal properties, in the prevention of the disorder by employing molecular docking techniques, conducting drug-likeness prediction assessments, and performing ADME analysis. Methods: Amyloid beta protein was retrieved from the PDB database. The ligands present on the leaf of the Ginkgo biloba plant were chosen based on previously existing studies in this domain. The compounds that had the potential to disrupt docking interactions and the ligands exhibiting weak binding affinity were eliminated. Subsequently, docking calculations were conducted using the PyRx tool. To assess the absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties, as well as druglikeness, an ADME and drug-likeness analysis was carried out employing the Swiss-ADME and ADMET Lab web server. Results: According to the docking results, Amentoflavone, Ginkgetin, Sciadopitysin, Bilobetin, Isoginkgetin, Kaempferol, and 6-Hydroxykynurenic acid had the highest binding affinities. Moreover, analysis of the ADMET profile and drug-likeness prediction revealed that Kaempferol and 6-Hydroxykynurenic acid were safe and possessed drug-like properties among these seven compounds. Conclusion: The present study suggests that Kaempferol and 6- Hydroxykynurenic acid have specific binding affinity and they could be effective against the amyloid beta protein. Also, these compounds can be used in therapeutic strategies against Alzheimer’s disease.
Keywords: ADME; Alzheimer’s disease; Amyloid-beta protein; ginko biloba; molecular docking